Risk factors and Response of Branch Retinal Vein Occlusion induced Macular Edema to intravitreal injections of Triamcinolone and Bevacizumab - Singhai Prakhar; Nema Nitin; Verma Sonam; Ravindra Kumar; Ankit Raj; Rajendra Malviya (Delhi Journal of Ophthalmology)
Background: Branch retinal vein occlusion (BRVO) is a common retinal vascular condition associated with systemic risk factors like hypertension and diabetes mellitus. It causes central visual loss primarily due to macular edema that responds to intravitreal injections of triamcinolone and bevacizumab. Aims: To find the risk factors and compare the effects of intravitreal injections of triamcinolone and bevacizumab in BRVO induced macular edema. Settings and Design: A tertiary eye center based prospective, interventional study. Materials and Methods: Patients of BRVO were evaluated for substance abuse and systemic vascular diseases. 40 eyes of 40 patients of BRVO received intravitreal injections of triamcinolone acetonide (IVTA, 4 mg/0.1 ml, 20 patients) or bevacizumab (IVB, 1.25 mg/0.1 ml, 20 patients) for macular edema. The patients were followed for 12 months. Best-corrected visual acuity and central macular thickness by optical coherence tomography were measured to assess the response to treatment. Statistical Analysis: Statistical package for the social sciences (SPSS) version 20.0 software was used to analyze the data. Wilcoxon signed rank test was performed to see the improvement in logMAR visual acuity after the treatment. Results: Hypertension was the commonest risk factor. Tobacco addiction, diabetes mellitus, hyperhomocyteinemia and dyslipidemia were other systemic associations of BRVO. Both IVTA and IVB were effective in reducing the macular edema and improving the vision at the end of 12-month follow-up period. Conclusion: Hypertension and tobacco use in various forms are important risk factors for BRVO. Both IVTA and IVB show comparable response to macular edema secondary to BRVO.